Improvement of gel quality of Surimi from Bigeye snapper (Priacanthus tayenus) - Yuwathida Kwalumtharn (Prince of Songkla University, 2022)
Thesis (M.Sc., Fishery Products Technology)--Prince of Songkla University, 2002